The Implementation of Qur'an Learning through The Ummi Method at Islamic Kindergarten Widya Cendekia - Elis Nur Megawati; Siti Jariyah; Siti Syaropah; Sulistiatun Hafifah; Firman Robiansyah (IJIE International Journal of Islamic Education, 2022)
This study aims to determine the learning of al-Qur’an through the Ummi method at Islamic Kindergarten Widya Cendekia. This research employs a qualitative research approach with a case study design. The data were obtained from the results of observations, interviews, and document reviews. The results showed that the application of the Ummi method carried out by Islamic Kindergarten Widya Cendekia in learning al-Qur’an had a good effect on children's ability to read al-Qur’an properly and correctly and increased their ability to memorize al-Qur'an. This can be seen from the response and behavior of students when learning al-Qur’an using the Ummi method. The students were able to follow the reading tonnes of Ummi and tajwid (the structure of Qur’an recitation). Certified teachers who routinely conduct training in learning the ummi method and the availability of teaching aids are both supportive and inhibiting factors in using the ummi method. The inhibiting factors in the implementation of the ummi method were that each group consisted of students who had different abilities or volume achievements, a lack of cooperation between parents and teachers in learning to read al-Qur’an, and a lack of teacher ability in managing Qur'an learning classes using the ummi method.